RELAÇÃO UNIVERSIDADE-ESCOLA NA FORMAÇÃO DOCENTE INICIAL | The relationship between university and the school in the initial formation of teachers (Trabalho & Educação, 2016)
The aim of this article is to think about the relationship between the university and the school for the initial formation of teachers as an essential process for the formative effectuation of the future teachers in the approach between theory and practice, in the dialogue of knowledge between institutions which are the mainly responsible for the formation of the teachers. The reflections which are shown here aim to (re)think about the relationship between the university and the school taking into consideration the actions of PIBID in the ambit of the Public Policies for Education as a program for initial and continued formation for teachers. The discussions of this article are based on the concept of university-school by Christophe Charle and Jacques Verger, and Maria de Lourdes Fávero. Taking into consideration the studies by Boaventura de Souza Santos e Maria Paula Meneses, it was discussed the concept of dialogue between different kinds of knowledge. Menga Lüdke was the reference for the discussions about the docent formation and Celina Souza about the concept of public policies. Finally, the documents of Coordination of Improvement of Higher Education Personnel in Brazil (CAPES) were the reference for the discussions about PIBID. The methodological procedures are characterized as an exploratory and descriptive research according to study by Maria Cecília Minayo and the approach for the documental analysis was realized according to studies by Laurence Bardin and by Bernadete Gatti. As a result, it is supported that PIBID has been a link between the university and the school, approximating and narrowing the necessity of (re)thinking about the initial formation of the docent from the formative and institutional relationships as places for the academic and human building. It is also observed the transforming the role that the university and the school have for the initial formation of teachers as protagonists of this process. Finally, it is highlighted the necessity of paradigmatic changes in the way teachers are formed nowadays. ___ O objetivo deste artigo é refletir sobre a importância da relação universidade-escola para a formação docente inicial como processo essencial para a efetivação formativa dos futuros docentes na aproximação entre teoria-prática, no diálogo de saberes entre instituições prioritariamente responsáveis pela formação de professores. As reflexões aqui apresentadas intencionam pensar e (re)pensar a relação universidade- escola à luz das ações do Programa Institucional de Bolsa de Iniciação à Docência (PIBID) no âmbito das políticas públicas de educação como programa de formação docente inicial e continuada. As discussões deste artigo fundamentam-se no conceito universidade-escola apresentados por Christophe Charle e Jacques Verger e por Maria de Lourdes Fávero; a partir da obra de Boaventura de Souza Santos e Maria Paula Meneses trabalhou-se com o conceito de diálogo de saberes; o trabalho de Menga Lüdke embasou as discussões sobre a formação docente; já a obra de Celina Souza o conceito de políticas públicas; e nos documentos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES) fundamentaram-se as discussões sobre o PIBID. Os procedimentos metodológicos caracterizaram-se como pesquisa exploratória, descritiva embasada no trabalho de Maria Cecília Minayo, com abordagem de análise documental a partir dos estudos de Laurence Bardin e Bernadete Gatti. Como resultados aponta-se que o PIBID tem se manifestado como elo entre a universidade-escola aproximando e estreitando a necessidade de (re)pensar a formação docente inicial a partir das relações formativas e institucionais como espaços de construção acadêmica e humana; observa-se ainda o papel transformador que universidade e escola têm na formação docente inicial como principais atrizes desse processo; reforça- se a necessidade de mudanças paradigmáticas em relação à formação de professores na atualidade.